2005
DOI: 10.1038/modpathol.3800307
|View full text |Cite
|
Sign up to set email alerts
|

Borderline epithelial tumors of the ovary

Abstract: The concept and terminology of borderline epithelial tumors of the ovary have been controversial for over a century, in spite of the acceptance of a borderline category in almost all current classifications of ovarian tumors. Typically, borderline tumors are noninvasive neoplasms that have nuclear abnormalities and mitotic activity intermediate between benign and malignant tumors of similar cell type. Borderline tumors of all surface epithelial cell types have been studied. The most common and best understood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
130
4
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(149 citation statements)
references
References 81 publications
4
130
4
11
Order By: Relevance
“…Borderline tumors may show peritoneal implants and lymphatic metastasis and these findings should not lead to an erroneous diagnosis of carcinoma in a morphologically borderline tumor. 14,22 Our cases however did not show any implants or metastasis.…”
Section: Borderline Epithelial Tumorsmentioning
confidence: 46%
See 1 more Smart Citation
“…Borderline tumors may show peritoneal implants and lymphatic metastasis and these findings should not lead to an erroneous diagnosis of carcinoma in a morphologically borderline tumor. 14,22 Our cases however did not show any implants or metastasis.…”
Section: Borderline Epithelial Tumorsmentioning
confidence: 46%
“…Microscopically, cells formed 3 or less layers with or without papillae over a continuous extent of at least 5mm. 4,21,22 Out of 6 cases, 5 cases were more than 40 years age and one case was below 40 years, all were unilateral and four cases were of size more than 10cms. In our study, three cases showed endocervical type of lining epithelium ( fig.2).…”
Section: Borderline Epithelial Tumorsmentioning
confidence: 99%
“…Especially for our assessment, this involves the often-used CT and MRI examinations. Moreover, the commonly observed tumour marker CA-125 -which is much less enhanced in BOTs than in ovarian cancers -does not suitably improve any positive or negative predictive value of the examination (Hart, 2005;Schmalfeldt and Pfisterer, 2007).…”
Section: Diagnosticsmentioning
confidence: 99%
“…Borderline tumours of the ovary constitute 8 -10% of all ovarian tumours. Having an incidence of 1.8 -4.8 out of 100 000 women per year, they belong to the seldom 'non-benign' epithelial ovarian tumours (Hart, 2005;Tinelli et al, 2006;Wong et al, 2007). In contrast to the case of ovarian carcinomas, most of the patients are diagnosed at an early stage I (Gotlieb et al, 2005;Yokoyama et al, 2006;Cusido et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation